High-dispersity superfine copper powder and preparation method thereof

The preparation of high-dispersible ultrafine copper powder through two-step method solves the problems of complex process, high energy consumption and poor copper powder quality in the existing technology, and realizes efficient and low-cost copper powder preparation, which is suitable for industrial production.

CN119387606APending Publication Date: 2025-02-07CHANGSHA PENGCHU NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411836688.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing preparation methods for ultrafine copper powder have problems such as complex process conditions, high energy consumption, low production capacity, poor monodispersity, wide particle size distribution, uneven size and poor crystallinity of copper powder.

Method used

The high dispersible ultrafine copper powder was prepared by two-step method. First, the copper-containing solution was mixed with the reducing agent to react to form a copper oxide pioneer, and then it was dispersed in water and mixed with the dispersant, and then washed, centrifuged and dried to obtain Highly dispersible ultrafine copper powder.

Benefits of technology

The production process is simplified, the reaction temperature and energy consumption are reduced, and the environmental pollution is reduced. The prepared copper powder is smooth on the surface, uniform in particle size distribution, high dispersion and high purity, and is suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387606A_ABST
    Figure CN119387606A_ABST
Patent Text Reader

Abstract

The invention provides high-dispersity superfine copper powder and a preparation method thereof, and belongs to the technical field of metal materials. The preparation method comprises the following steps: mixing a copper-containing solution, an alkali-containing solution and a reducing agent solution, and reacting to obtain a cuprous oxide precursor; and mixing the cuprous oxide precursor solution, the dispersing agent solution and the reducing agent solution, and reacting to obtain the superfine copper powder. According to the method, a traditional one-step liquid phase synthesis method for the superfine copper powder is abandoned, a two-step method is creatively adopted for preparing the superfine copper powder, and the contradiction between the size of copper particles and the technological capacity is solved. According to the preparation method, the copper particles with smaller sizes can be prepared on the premise that high unit volume productivity is kept, and the prepared copper particles are smooth in surface and uniform in size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal materials, and in particular to a highly dispersible ultrafine copper powder and a preparation method thereof. Background Art

[0002] Ultrafine copper powder has broad application prospects in the fields of civil, industry, and national defense. Since it was first discovered in 1995 that ultrafine copper powder has very low resistance, its performance has become a hot topic in the electronics industry. Due to its small size, it exhibits many excellent properties, especially electrical conductivity, thermal conductivity, specific surface area, etc., and has broad application prospects in the fields of electronics, optoelectronics, plasmon optics, catalysis, thermoelectricity, sensing, biomedicine, etc. For example, in addition to silver and gold, copper nanocrystals can also cause localized surface plasmon resonance (LSPR) in the visible and near-infrared regions; in addition, polymer coatings based on copper nanowires are expected to replace indium tin oxide films (ITO) and have broad application prospects in the fields of touch screen displays and transparent conductive electrodes; copper nanoparticles can also be used as commercial catalysts in water gas conversion, detoxification, and other fields; high-purity copper powder has an irreplaceable position in the production and packaging of semiconductors and high-density printed circuit boards (PCBs). In addition, ultrafine copper powder can also be used as a lubricant additive for automobile engines to reduce starting current and increase cylinder pressure. It can also form a protective film on the cylinder liner and piston ring to ensure long-term safe operation of the vehicle in the event of lubrication system failure. Therefore, ultrafine copper powder is expected to replace precious metals in the application of high-efficiency catalysts, conductive slurries, conductive adhesives and high-grade lubricants. It can significantly reduce production costs and has a good application prospect.

[0003] At present, the preparation methods of ultrafine copper powder include thermal decomposition method, sol-gel method, liquid phase reduction method, ball milling method, vapor deposition method and electrochemical method. However, the current copper powder preparation methods generally have the disadvantages of complex process conditions, high energy consumption, low process capacity, poor monodispersity of the obtained copper powder, wide particle size distribution, uneven size and poor crystallinity. Therefore, how to provide a method for preparing ultrafine copper powder with low cost, simple method and uniform product size has become a problem that technicians in this field need to solve urgently. Summary of the invention

[0004] The purpose of the present invention is to provide a highly dispersible ultrafine copper powder and a preparation method thereof, so as to solve the technical problems existing in the existing preparation methods of ultrafine copper powder, such as complex process conditions, high energy consumption, low process capacity, poor monodispersity of the obtained copper powder, wide particle size distribution, uneven size and poor crystallinity.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing highly dispersible ultrafine copper powder, comprising the following steps:

[0007] 1) mixing a copper-containing solution with a reducing agent solution and reacting the mixture to obtain a cuprous oxide precursor;

[0008] 2) dispersing the cuprous oxide precursor obtained in step 1) in water to obtain a cuprous oxide precursor solution, mixing it with a dispersant solution to obtain a mixed solution, adding a reducing agent solution to react, and then washing, centrifuging and drying in sequence to obtain a highly dispersible ultrafine copper powder;

[0009] In step 2), the dispersant in the dispersant solution includes one or more of gelatin, gum arabic, polyvinyl pyrrolidone, sodium lauryl sulfate, hexadecyltrimethylammonium bromide, cellulose derivatives and fatty acid polyethylene glycol esters.

[0010] Further, in step 1), the copper-containing solution includes one or more of a copper sulfate solution, a copper nitrate solution, a copper chloride solution, a copper hydroxide solution, a copper acetate solution and a basic copper carbonate solution;

[0011] In step 1) and step 2), the reducing agent in the reducing agent solution independently includes one or more of sodium borohydride, sodium hypophosphite, glucose, formaldehyde, hydrazine hydrate, hydrogen peroxide, L-ascorbic acid, lithium borohydride, thiourea dioxide, potassium borohydride and ferrous citrate.

[0012] Furthermore, in step 1), the concentration of the copper-containing solution is 0.1-1.5 mol / L, and the pH value of the copper-containing solution is 6-13.

[0013] Furthermore, in step 1), the molar ratio of the reducing agent to the copper element in the reducing agent solution is 0.4 to 2:1;

[0014] The volume ratio of the copper-containing solution to the reducing agent solution is 100-500:50-200.

[0015] Furthermore, in step 1), the reaction temperature is 40-90° C., the reaction time is 0.5-4 h, and the reaction is carried out under stirring at a stirring speed of 300-600 rpm.

[0016] Furthermore, in step 2), the mass concentration of the cuprous oxide precursor solution is 0.05-10%;

[0017] The molar ratio of the reducing agent in the reducing agent solution to the copper ions in the cuprous oxide precursor solution is 0.1 to 20:1;

[0018] The pH value of the mixed solution is 6-13.

[0019] Furthermore, in step 2), the concentration of the dispersant solution is 0.1 to 100 mmol / L.

[0020] Furthermore, in step 2), the power of the dispersion is 100 to 150 W, and the dispersion time is 15 to 30 min;

[0021] The reaction temperature is 40-90° C., the reaction time is 1-6 hours, and the reaction is carried out under stirring at a stirring speed of 300-600 rpm.

[0022] Furthermore, in step 2), the centrifugal speed is 8000-10000 rpm, and the centrifugal time is 3-8 min;

[0023] The drying temperature is 50-80°C and the drying time is 12-48 hours.

[0024] The invention provides highly dispersible ultrafine copper powder prepared by the above preparation method. The copper powder particles are regular spherical and the particle size of the copper powder is 0.1-0.5 μm.

[0025] Beneficial effects of the present invention:

[0026] The steps for preparing the ultrafine copper powder of the present invention are simple to operate. Compared with the traditional process, the present invention simplifies the production process, has milder reaction conditions, reduces the reaction temperature, reduces energy consumption, and reduces pollution to the environment;

[0027] The ultrafine copper powder prepared by the invention has a smooth surface, uniform particle size distribution, high dispersibility, good morphology consistency, and a purity of more than 99% and a tap density of 3.5-4.5 g / cm 3 ;

[0028] The present invention abandons the traditional one-step method of directly reducing copper ions to copper, and adopts a unique two-step method to prepare ultrafine copper powder, which comprises two steps of pre-reducing copper ions to generate cuprous oxide and then reducing cuprous oxide to generate ultrafine copper powder. Therefore, the ultrafine copper powder prepared by the present invention has a smaller particle size and a higher production capacity per unit volume, and is more conducive to industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of the process of preparing ultrafine copper powder according to the present invention;

[0030] Figure 2 is a SEM morphology of the cuprous oxide precursor prepared in Example 1;

[0031] Figure 3 is a SEM morphology image of the ultrafine copper powder prepared in Example 1 at a low magnification;

[0032] Figure 4 is a SEM morphology image of the ultrafine copper powder prepared in Example 1 at a high magnification;

[0033] Figure 5 is a statistical result diagram of the physical size distribution of the ultrafine copper powder prepared in Example 1;

[0034] Figure 6 1 is an XRD characterization result diagram of the ultrafine copper powder prepared in Example 1;

[0035] Figure 7 is a SEM morphology of the cuprous oxide precursor prepared in Example 2;

[0036] Figure 8 is a SEM morphology image of the ultrafine copper powder prepared in Example 2 at a low magnification;

[0037] Fig. 9 is a SEM morphology image of the ultrafine copper powder prepared in Example 2 at a high magnification;

[0038] Fig.10 is a statistical result diagram of physical size distribution of ultrafine copper powder prepared in Example 2;

[0039] Fig.11 is the XRD characterization result diagram of the ultrafine copper powder prepared in Example 2;

[0040] Fig.12 is a SEM morphology of the cuprous oxide precursor prepared in Example 3;

[0041] Fig.13 is a SEM morphology image of the ultrafine copper powder prepared in Example 3 at a low magnification;

[0042] Fig.14 is a SEM morphology image of the ultrafine copper powder prepared in Example 3 at a high magnification;

[0043] Fig.15 is a statistical result diagram of physical size distribution of ultrafine copper powder prepared in Example 3;

[0044] Fig.16 is the XRD characterization result diagram of the ultrafine copper powder prepared in Example 3;

[0045] Fig.17 This is the SEM morphology of the copper powder finally obtained in Comparative Example 1. DETAILED DESCRIPTION

[0046] The present invention provides a method for preparing highly dispersible ultrafine copper powder, comprising the following steps:

[0047] 1) mixing a copper-containing solution with a reducing agent solution and reacting the mixture to obtain a cuprous oxide precursor;

[0048] 2) dispersing the cuprous oxide precursor obtained in step 1) in water to obtain a cuprous oxide precursor solution, mixing it with a dispersant solution to obtain a mixed solution, adding a reducing agent solution to react, and then washing, centrifuging and drying in sequence to obtain a highly dispersible ultrafine copper powder;

[0049] In step 2), the dispersant in the dispersant solution includes one or more of gelatin, gum arabic, polyvinyl pyrrolidone, sodium lauryl sulfate, hexadecyltrimethylammonium bromide, cellulose derivatives and fatty acid polyethylene glycol esters.

[0050] In the present invention, the dispersant is preferably one or more of gelatin, gum arabic, polyvinyl pyrrolidone, sodium lauryl sulfate and cetyltrimethylammonium bromide, further preferably one or more of gelatin, gum arabic and cetyltrimethylammonium bromide, more preferably cetyltrimethylammonium bromide.

[0051] In the present invention, in step 1), the copper-containing solution comprises one or more of a copper sulfate solution, a copper nitrate solution, a copper chloride solution, a copper hydroxide solution, a copper acetate solution and a basic copper carbonate solution, preferably one or more of a copper sulfate solution, a copper nitrate solution and a basic copper carbonate solution, further preferably a copper sulfate solution and / or a copper nitrate solution, more preferably a copper sulfate solution;

[0052] In step 1) and step 2), the reducing agent in the reducing agent solution independently includes one or more of sodium borohydride, sodium hypophosphite, glucose, formaldehyde, hydrazine hydrate, hydrogen peroxide, L-ascorbic acid, lithium borohydride, thiourea dioxide, potassium borohydride and ferrous citrate, preferably one or more of sodium borohydride, sodium hypophosphite, glucose, hydrazine hydrate and L-ascorbic acid, further preferably one or more of sodium borohydride, L-ascorbic acid and hydrazine hydrate, more preferably L-ascorbic acid.

[0053] In the present invention, in step 1), the concentration of the copper-containing solution is 0.1-1.5 mol / L, preferably 0.5-1.2 mol / L, more preferably 0.75-1 mol / L, more preferably 0.8 mol / L, and the pH value of the copper-containing solution is 6-13, preferably 7-12, more preferably 8-10, and more preferably 9.

[0054] In the present invention, in step 1), the molar ratio of the reducing agent to the copper element in the reducing agent solution is 0.4 to 2:1, preferably 0.8 to 1.95:1, and more preferably 1.875:1;

[0055] The volume ratio of the copper-containing solution to the reducing agent solution is 100-500:50-200, preferably 150-450:80-160, more preferably 200-400:100-150, and more preferably 300:120.

[0056] In the present invention, in step 1), the reaction temperature is 40-90°C, preferably 50-85°C, more preferably 60-80°C, more preferably 70°C, the reaction time is 0.5-4h, preferably 1-3.5h, more preferably 2-3h, more preferably 2.5h, the reaction is carried out under stirring, and the stirring speed is 300-600rpm, preferably 400-550rpm, more preferably 450-500rpm, more preferably 475rpm.

[0057] In the present invention, in step 2), the mass concentration of the cuprous oxide precursor solution is 0.05-10%, preferably 1-8%, more preferably 2-5%, and more preferably 4%;

[0058] The molar ratio of the reducing agent in the reducing agent solution to the copper ions in the cuprous oxide precursor solution is 0.1 to 20:1, preferably 1 to 18:1, more preferably 5 to 15:1, and more preferably 10:1;

[0059] The pH value of the mixed solution is 6-13, preferably 7-12, more preferably 8-10, and even more preferably 9.

[0060] In the present invention, the volume ratio of the cuprous oxide precursor solution, the dispersant solution and the reducing agent solution is 100-300:50-200:100-300, preferably 140-260:80-160:140-260, more preferably 180-220:100-140:180-220, and more preferably 200:120:200.

[0061] In the present invention, the alkaline solution for adjusting the pH value of the system is preferably a sodium hydroxide solution or an ammonia solution, and more preferably a sodium hydroxide solution;

[0062] The concentration of the alkali-containing solution is 0.1 to 10 mol / L, preferably 1 to 8 mol / L, more preferably 2 to 6 mol / L, and even more preferably 4 mol / L.

[0063] In the present invention, in step 2), the concentration of the dispersant solution is 0.1 to 100 mmol / L, preferably 1 to 70 mmol / L, more preferably 5 to 50 mmol / L, and more preferably 25 mmol / L.

[0064] In the present invention, in step 2), the power of the dispersion is 100 to 150 W, and the dispersion time is 15 to 30 min;

[0065] The reaction temperature is 40-90°C, preferably 50-85°C, further preferably 60-80°C, more preferably 70°C, the reaction time is 1-6h, preferably 2-5h, further preferably 3-4h, more preferably 3.5h, the reaction is carried out under stirring, and the stirring speed is 300-600rpm, preferably 350-550rpm, further preferably 400-500rpm, more preferably 450rpm.

[0066] In the present invention, in step 2), the centrifugal speed is 8000-10000 rpm, preferably 9000 rpm, and the centrifugal time is 3-8 min, preferably 5 min;

[0067] The drying temperature is 50 to 80° C., preferably 60 to 77° C., more preferably 65 to 70° C., more preferably 68° C., and the drying time is 12 to 48 h, preferably 18 to 36 h, more preferably 24 to 32 h, more preferably 28 h.

[0068] In the present invention, the drying treatment method includes spray drying, freeze drying, vacuum drying or drying under inert atmosphere protection, preferably spray drying, freeze drying or vacuum drying, and more preferably vacuum drying.

[0069] The present invention provides highly dispersible ultrafine copper powder prepared by the above preparation method, wherein the copper powder particles are regular spherical, and the particle size of the copper powder is 0.1-0.5 μm, preferably 150nm-400nm, further preferably 200nm-350nm, and more preferably 300nm.

[0070] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0071] Example 1

[0072] 40 g of copper sulfate pentahydrate was dissolved in 100 mL of water in a 120 W ultrasonic system to obtain a copper sulfate solution, and the solution was stirred at 500 rpm, and 0.5 mol / L of sodium hydroxide solution was slowly added thereto to adjust the pH value of the copper sulfate solution to 9; the copper sulfate solution was heated to 80° C. and mechanically stirred at 500 rpm, and then 50 mL of a glucose solution with a concentration of 54 g / 50 mL was injected into the copper sulfate solution within 30 seconds, and a cuprous oxide precursor was obtained after reacting for 2 hours;

[0073] 10 g of the washed cuprous oxide precursor was added to 100 mL of water, and the mixture was dispersed by ultrasonic treatment at a power of 120 W for 20 min to obtain a cuprous oxide precursor solution; 50 mL of a 1 g / 50 mL hexadecyltrimethylammonium bromide solution was directly poured into the cuprous oxide precursor solution at a rotation speed of 500 rpm, and the mixture was stirred to obtain a mixed solution; a 0.5 mol / L sodium hydroxide solution was slowly added dropwise to the mixed solution to adjust the pH value of the mixed solution to 10; the mixed solution was stirred at 400 rpm for 2 h. The liquid was heated to 80°C, put into an oil bath, and mechanically stirred at a speed of 600 rpm, and then 100 mL of ascorbic acid solution with a concentration of 20 g / 100 mL was directly poured into the mixed solution and reacted for 2 hours to obtain nano copper particles with a particle size of about 350 nm. The nano copper particles were then washed with pure water and ethanol for 3 times each, and the washed copper powder particles were centrifuged at a speed of 9000 rpm and placed in a vacuum oven. Highly dispersible ultrafine copper powder was obtained.

[0074] The copper powder prepared in this embodiment has a smooth surface and a small size. The prepared electronic copper slurry has excellent performance, an oil absorption value of 8%, and a scraper fineness of less than 1 micron.

[0075] Example 2

[0076] 40 g of copper sulfate pentahydrate was dissolved in 100 mL of water in a 120 W ultrasonic system to obtain a copper sulfate solution, and the solution was stirred at 500 rpm, and 0.5 mol / L of sodium hydroxide solution was slowly added thereto to adjust the pH value of the copper sulfate solution to 10; the copper sulfate solution was heated to 80° C. and mechanically stirred at 500 rpm, and then 50 mL of a 27 g / 50 mL glucose solution was injected into the copper sulfate solution within 30 s, and a cuprous oxide precursor was obtained after reacting for 2 h;

[0077] 10 g of the washed cuprous oxide precursor was added to 100 mL of water, and the mixture was dispersed by ultrasonic treatment at a power of 120 W for 20 min to obtain a cuprous oxide precursor solution; 50 mL of a 1 g / 50 mL hexadecyltrimethylammonium bromide solution was directly poured into the cuprous oxide precursor solution at a rotation speed of 500 rpm, and the mixture was stirred to obtain a mixed solution; a 0.5 mol / L sodium hydroxide solution was slowly added dropwise to the mixed solution to adjust the pH value of the mixed solution to 11; the mixed solution was stirred to obtain a mixed solution; The solution was heated to 80°C, placed in an oil bath, and mechanically stirred at 600 rpm. Then, 100 mL of 20 g / 100 mL glucose solution was directly poured into the mixed solution and reacted for 2 hours to obtain nano-copper particles with a particle size of about 400 nm. The nano-copper particles were then washed with pure water and ethanol for 4 times each. The washed copper powder particles were centrifuged at 9000 rpm and placed in a vacuum oven. They were vacuum dried at 65°C for 24 hours to obtain highly dispersible ultrafine copper powder.

[0078] Example 3

[0079] 40 g of copper sulfate pentahydrate was dissolved in 100 mL of water in a 120 W ultrasonic system to obtain a copper sulfate solution, and the solution was stirred at 500 rpm, and 0.5 mol / L of sodium hydroxide solution was slowly added thereto to adjust the pH value of the copper sulfate solution to 9; the copper sulfate solution was heated to 80° C. and mechanically stirred at 500 rpm, and then 50 mL of a glucose solution with a concentration of 32 g / 50 mL was injected into the copper sulfate solution within 30 seconds, and a cuprous oxide precursor was obtained after reacting for 2 hours;

[0080] 10 g of the washed cuprous oxide precursor was added to 100 mL of water, and the mixture was dispersed by ultrasonic treatment at a power of 120 W for 20 min to obtain a cuprous oxide precursor solution; 50 mL of a 1 g / 50 mL hexadecyltrimethylammonium bromide solution was directly poured into the cuprous oxide precursor solution at a rotation speed of 500 rpm, and the mixture was stirred to obtain a mixed solution; a 0.5 mol / L sodium hydroxide solution was slowly added dropwise to the mixed solution to adjust the pH value of the mixed solution to 10; the mixed solution was stirred to obtain a mixed solution; The solution was heated to 80°C, placed in an oil bath, and mechanically stirred at 600 rpm. Then, 100 mL of 20 g / 100 mL ferrous citrate solution was directly poured into the mixed solution and reacted for 2 h to obtain nano-copper particles with a particle size of 300 nm. The nano-copper particles were then washed with pure water and ethanol for 5 times each. The washed copper powder particles were centrifuged at 9000 rpm and placed in a vacuum oven. They were vacuum dried at 65°C for 24 h to obtain highly dispersible ultrafine copper powder.

[0081] Example 4

[0082] 200 g of copper nitrate was dissolved in 200 mL of water in a 120 W ultrasonic system to obtain a copper nitrate solution, and the solution was stirred at 500 rpm, and 0.5 mol / L of sodium hydroxide solution was slowly added thereto to adjust the pH value of the copper nitrate solution to 9; the copper nitrate solution was heated to 40° C. and mechanically stirred at 600 rpm, and then 150 mL of a glucose solution with a concentration of 135 g / 150 mL was injected into the copper nitrate solution within 30 seconds, and a cuprous oxide precursor was obtained after reacting for 2 hours;

[0083] 10 g of the washed cuprous oxide precursor was added to 100 mL of water, and the mixture was dispersed by ultrasonic treatment at a power of 120 W for 20 min to obtain a cuprous oxide precursor solution; 50 mL of a 1 g / 50 mL hexadecyltrimethylammonium bromide solution was directly poured into the cuprous oxide precursor solution at a rotation speed of 600 rpm, and the mixture was stirred to obtain a mixed solution; a 0.5 mol / L sodium hydroxide solution was slowly added dropwise to the mixed solution to adjust the pH value of the mixed solution to 10; the mixed solution was stirred to obtain a mixed solution; the mixture ... The solution was heated to 80°C, placed in an oil bath, and mechanically stirred at 600 rpm. Then, 100 mL of 25 g / 100 mL ascorbic acid solution was directly poured into the mixed solution and reacted for 2 h to obtain nano-copper particles with a particle size of 350 nm. The nano-copper particles were then washed with pure water and ethanol for 5 times each. The washed copper powder particles were centrifuged at 9000 rpm and placed in a vacuum oven. They were vacuum dried at 65°C for 24 h to obtain highly dispersible ultrafine copper powder.

[0084] Comparative Example 1

[0085] 40 g of copper sulfate pentahydrate was dissolved in 200 mL of water to obtain a copper sulfate solution, and the solution was stirred at 500 rpm, and 0.5 mol / L of sodium hydroxide solution was slowly added thereto to adjust the pH value of the copper sulfate solution to 9; the copper sulfate solution was heated to 80°C and mechanically stirred at 500 rpm, and then 150 mL of an ascorbic acid solution with a concentration of 40 g / 150 mL was injected into the copper sulfate solution at a rate of 100 mL / min, and copper particles were obtained after reacting for 2 hours; the copper particles were washed with pure water and ethanol for 3 times each, and then the copper particles were centrifuged at 9000 rpm, and then placed in a vacuum oven and vacuum dried at 65°C for 24 hours.

[0086] In contrast, the copper powder prepared in this comparative example has a rough surface and severe agglomeration, and the performance of the prepared electronic copper slurry is poor, with an oil absorption value as high as 10.4% and a scraper fineness much greater than 3 microns.

[0087] It can be seen from the above embodiments that the present invention provides a highly dispersible ultrafine copper powder and a preparation method thereof. Figure 2This is the SEM morphology of the cuprous oxide precursor prepared in Example 1. It can be seen that when more glucose is added and the pH value is low, the cuprous oxide is mostly regular spherical, has good dispersibility, and has a small particle size; Figure 4 This is a SEM morphology of the ultrafine copper powder prepared in Example 1 at a high magnification. It can be seen from the figure that the copper particles have a smooth surface, good dispersion, and are mostly regular spherical, with a particle size distribution of about 350nm; Figure 5 1 is a statistical result diagram of the physical size distribution of the ultrafine copper powder prepared in Example 1. It can be seen that the size distribution of the copper particles ranges from 100 nm to 550 nm, and some of the particle sizes are larger, but mainly concentrated around 350 nm;

[0088] Figure 7 This is the SEM morphology of the cuprous oxide precursor prepared in Example 2. It can be seen that when less glucose is added and the pH value is higher, the cuprous oxide is partially in a regular spherical shape, partially in a polyhedral shape and has poorer dispersibility, and the particle size distribution is less concentrated; Fig. 9 This is a SEM morphology of the ultrafine copper powder prepared in Example 2 at a high magnification. It can be seen from the figure that the copper particles have a smooth surface, good dispersion, and are mostly regular spherical, with a particle size distribution of about 400 nm. Fig.10 1 is a statistical result diagram of the physical size distribution of the ultrafine copper powder prepared in Example 2. It can be seen that the size distribution of the copper particles ranges from 100 nm to 750 nm, and some of the particle sizes are larger, but mainly concentrated around 400 nm;

[0089] Fig.14 This is a SEM morphology of the ultrafine copper powder prepared in Example 3 at a high magnification. It can be seen from the figure that the copper particles have a smooth surface, good dispersion, and are mostly regular spherical, with a particle size distribution of about 300 nm; Fig.15 1 is a statistical result diagram of the physical size distribution of the ultrafine copper powder prepared in Example 3. It can be seen that the size distribution of the copper particles ranges from 150nm to 450nm, and is mainly concentrated around 300nm.

[0090] Fig.17 This is a SEM morphology of the copper powder finally obtained in Example 1. It can be seen from the figure that the size of the obtained copper powder is micron-level, large in size, and poor in dispersibility, which is also one of the limitations of the one-step synthesis of copper powder.

[0091] In summary, the present invention provides a highly dispersible ultrafine copper powder and a preparation method thereof, abandoning the traditional one-step liquid phase synthesis method of ultrafine copper powder, creatively adopting a two-step method to prepare ultrafine copper powder, and solving the contradiction between the size of copper particles and process capacity. The present invention can prepare smaller copper particles while maintaining a higher unit volume capacity, and the prepared copper particles have a smooth surface and uniform size.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing highly dispersible ultrafine copper powder, characterized in that: The following steps are involved: 1) mixing a copper-containing solution with a reducing agent solution and reacting the mixture to obtain a cuprous oxide precursor; 2) dispersing the cuprous oxide precursor obtained in step 1) in water to obtain a cuprous oxide precursor solution, mixing it with a dispersant solution to obtain a mixed solution, adding a reducing agent solution to react, and then washing, centrifuging and drying in sequence to obtain a highly dispersible ultrafine copper powder; In step 2), the dispersant in the dispersant solution includes one or more of gelatin, gum arabic, polyvinyl pyrrolidone, sodium lauryl sulfate, hexadecyltrimethylammonium bromide, cellulose derivatives and fatty acid polyethylene glycol esters.

2. The method for preparing a highly dispersible ultrafine copper powder according to claim 1, characterized in that: In step 1), the copper-containing solution includes one or more of a copper sulfate solution, a copper nitrate solution, a copper chloride solution, a copper hydroxide solution, a copper acetate solution and a basic copper carbonate solution; In step 1) and step 2), the reducing agent in the reducing agent solution independently includes one or more of sodium borohydride, sodium hypophosphite, glucose, formaldehyde, hydrazine hydrate, hydrogen peroxide, L-ascorbic acid, lithium borohydride, thiourea dioxide, potassium borohydride and ferrous citrate.

3. The method for preparing a highly dispersible ultrafine copper powder according to claim 1, characterized in that: In step 1), the concentration of the copper-containing solution is 0.1-1.5 mol / L, and the pH value of the copper-containing solution is 6-13.

4. The method for preparing a highly dispersible ultrafine copper powder according to claim 1 or 3, characterized in that: In step 1), the molar ratio of the reducing agent to the copper element in the reducing agent solution is 0.4 to 2:1; The volume ratio of the copper-containing solution to the reducing agent solution is 100-500:50-200.

5. The method for preparing a highly dispersible ultrafine copper powder according to claim 4, characterized in that: In step 1), the reaction temperature is 40-90° C., the reaction time is 0.5-4 h, and the reaction is carried out under stirring at a stirring speed of 300-600 rpm.

6. The method for preparing a highly dispersible ultrafine copper powder according to claim 1, characterized in that: In step 2), the mass concentration of the cuprous oxide precursor solution is 0.05-10%; The molar ratio of the reducing agent in the reducing agent solution to the copper ions in the cuprous oxide precursor solution is 0.1 to 20:1; The pH value of the mixed solution is 6-13.

7. The method for preparing a highly dispersible ultrafine copper powder according to claim 1 or 6, characterized in that: In step 2), the concentration of the dispersant solution is 0.1 to 100 mmol / L.

8. The method for preparing a highly dispersible ultrafine copper powder according to claim 1, characterized in that: In step 2), the power of the dispersion is 100-150W, and the dispersion time is 15-30min; The reaction temperature is 40-90° C., the reaction time is 1-6 hours, and the reaction is carried out under stirring at a stirring speed of 300-600 rpm.

9. The method for preparing a highly dispersible ultrafine copper powder according to claim 1, characterized in that: In step 2), the centrifugal speed is 8000-10000 rpm, and the centrifugal time is 3-8 min; The drying temperature is 50-80°C and the drying time is 12-48 hours.

10. The highly dispersible ultrafine copper powder prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The copper powder particles are regular spherical, and the particle size of the copper powder is 0.1 to 0.5 μm.

Citation Information

Patent Citations

  • Method for preparing superfine copper powder

    CN101195170A

  • Superfine copper powder and preparation method thereof

    CN103302297A

  • Method for producing copper powder, copper powder, and copper paste

    CN105026079A

  • Production of cuprous oxide powder and copper powder

    JP1993221637A

  • Superfine Copper Powder Slurry and Production Method Thereof

    US20080004358A1

Cited By

  • Blocky stacked spherical copper powder and preparation method thereof

    CN120421526A

  • Spherical-like copper powder and preparation method and application thereof

    CN120901295A

  • A method for preparing a high-conductivity sheet-shaped nanometer-thickness copper powder

    CN122703010A